Ethics and politics in school leadership : finding common ground - Brierton, Jeffrey T.; Graham, Brenda F.;Tomal, Daniel R.;Wilhite, Robert K. (Lanham, Maryland : Rowman & Littlefield, 2016)
The authors are national school resource experts and have teamed up to write a comprehensive book on ethics and politics. It covers everything you need to know about ethical leadership and dealing with politics in schools. The book starts with an ethical framework and moves on to politics with unions, administrators, and School Boards with suggested strategies for effective conflict resolution. There are realistic cases in every chapter of the book with the final chapter focused on comprehensive ethical and political cases to test the reader in addressing such issues in the educational or related settings.
1. Doing the right thing: ethics and school leadership -- 2. Ethics, politics and policies -- 3. Making haste slowly: politics at the district and board levels -- 4. Leading from the front: politics in the school building -- 5. Who's in charge here?: the politics of the union-administration relationship -- 6. The art of the possible: negotiating and communicating with people -- 7. Ethics and politics case studies.
Includes bibliographical references and index.
Keywords: SCHOOL ADMINISTRATORS -- PROFESSIONAL ETHICS